Role of home nurturing environment on early childhood neurodevelopment: a community-based survey in Shanghai, China - Chunhua Jiang; Xingying Li; Bing-Cheng Du; Jun Huang; Yun Li; Ying Zhang; Muxin Wei; Xiaoxi Xu; Yulin Yang; Hong Jiang (BMC, 2024)
Abstract Background Ages of 0-3 years are critical stages for children's neurodevelopment. However, the impact of the home nurturing environment on early childhood neurodevelopment remains unclear. Objective To explore the role of the home nurturing environment on early childhood neurodevelopment and to provide evidence of an association between fostering quality home nurturing and achieving optimal neurodevelopment. Participants and setting An online cross-sectional survey using the stratified sampling method was conducted from 16 June, 2021 to 18, February, 2022 in all 13 communities of Minhang District, Shanghai. A total of 2,402 children aged 0-3 years with balanced sex distribution were included. Methods The quality of home nurturing environments was measured using validated Child Home Nurture Environment Scales. Neurodevelopment was measured using the Ages and Stages Questionnaire - Third edition (ASQ-3). Generalized Linear Mixed Modeling was used to analyze the association between the quality of home nurturing environments and neurodevelopment. Results Among children aged 0-1, neglect or restriction was reported as the most prevalent problem (8.02%) among home nurturing environment dimensions, and was associated with an increased risk of suspected fine motor development delay (OR = 2.82, 95% CI: 1.18-6.69, P = 0.019). Among children aged 1-3, inadequate parental warmth, as the foremost (16.10%) problem, was associated with an increased risk of suspected gross motor development delay (OR = 4.12, 95% CI: 1.35-12.53, P = 0.013) and suspected personal-social development delay (OR = 12.50, 95%CI: 1.48-105.36, P = 0.020). Conclusions Poor home nurturing environments were associated with an increased risk of suspected early childhood neurodevelopment delay. There exists a need for services to guide for establishing a quality home nurturing environment.